Combination of Atractylenolide I, Atractylenolide III, and Paeoniflorin promotes angiogenesis and improves neurological recovery in a mouse model of ischemic Stroke - Haiyan Li; Wantong Yu; Yong Yang; Sijie Li; Jun Xu; Chen Gao; Wei Zhang; Wenjie Shi; Kunlin Jin; Xunming Ji; Changhong Ren (BMC, 2024)
Abstract Background Prognosis is critically important in stroke cases, with angiogenesis playing a key role in determining outcomes. This study aimed to investigate the potential protective effects of Atractylenolide I (Atr I), Atractylenolide III (Atr III), and Paeoniflorin (Pae) in promoting angiogenesis following cerebral ischemia. Methods The bEnd.3 cell line was used to evaluate the effects of these three compounds on vascular endothelial cell proliferation, migration, and tube formation. Male C57BL/6 mice underwent transient middle cerebral artery occlusion (MCAO), followed by daily intragastric administration of the Chinese medicine compounds to assess their impact on brain protection and angiogenesis. In vivo experiments included measuring infarct size and assessing neurological function. Immunofluorescence staining and an angiogenesis antibody array were used to evaluate angiogenesis in ischemic brain tissue. Functional enrichment analysis was performed to further investigate the pathways involved in the protective effects of the compounds. Molecular docking analysis explored the potential binding affinity of the compounds to insulin-like growth factor 2 (IGF-2), and Western blotting was used to measure levels of angiogenesis-related proteins. Results In vitro, the combination of Atr I, Atr III, and Pae enhanced cell proliferation, promoted migration, and stimulated tube formation. In vivo, the combined treatment significantly facilitated neurological function recovery and angiogenesis by day 14. The treatment also increased levels of angiogenesis-related proteins, including IGF-2. Pearson correlation analysis revealed a strong positive association between IGF-2 levels in ischemic brain tissue and angiogenesis, suggesting a good affinity of the compounds for the IGF-2 binding site, as supported by molecular docking analysis. Conclusion The administration of Atr I, Atr III, and Pae has shown significant enhancements in long-term stroke recovery in mice, likely due to the promotion of angiogenesis via increased activation of the IGF-2 pathway in ischemic brain tissue. Graphical Abstract